Immunopharmacological potential of Arctium lappa L. in immune-mediated skin diseases: A critical review of experimental and clinical evidence - Yang, Mengyao; Peng, Ge; Abudouwanli, Alafate; Wang, Shan; Sun, Quan; Zhao, Wanchen; Tan, Yi; Du, Xuefei; Zhang, Li; Ogawa, Hideoki; Okumura, Ko; Gao, Xinghua; et al. (Frontiers in Pharmacology, 2025)
BackgroundArctium lappa L. (A. lappa) has been used in traditional medicine worldwide and is increasingly being investigated for its immunomodulatory and anti-inflammatory effects. However, its therapeutic relevance for immune-mediated skin diseases (IMSDs) remains incompletely defined.ObjectiveThis review critically evaluates experimental and clinical evidence on A. lappa and its major lignans, arctiin and arctigenin, in IMSDs, including those associated with atopic dermatitis (AD), psoriasis, systemic lupus erythematosus (SLE), alopecia, systemic sclerosis (SSc), and vasculitis.MethodsWe systematically searched PubMed, Web of Science, and Scopus up to July 2025 using defined keywords. Eligible studies included in vitro, in vivo, and clinical investigations assessing the immunological and dermatological outcomes of A. lappa extracts or purified metabolites.ResultsPreclinical studies have demonstrated that A. lappa extracts and their lignans modulate key inflammatory pathways, including the NF-κB, JAK/STAT, and NLRP3 inflammasome signaling pathways. Evidence indicates protective effects on keratinocyte hyperproliferation, mast cell activation, dermal fibroblast fibrosis, and vascular endothelial inflammation. However, most data are derived from in vitro or murine models using heterogeneous preparations, with limited clinical validation. Reported doses range from 10–100 μM in cell assays to 15–100 mg/kg in animal studies, but pharmacokinetic and safety data remain insufficient.ConclusionA. lappa shows promising immunopharmacological potential for IMSDs, but the evidence remains preliminary. The current literature is limited by variability in extract preparation, a lack of standardized dosing, and the absence of robust randomized clinical trials. Future research should prioritize standardized phytochemical characterization, translational animal models, pharmacokinetic studies, and controlled clinical investigations to establish efficacy and safety.